Insulin resistance and insulin action - Crespo Retes, Isaac (2015)
It is important to recognize insulin resistance syndrome, frequently called the occidental civilization disease. Predominance of these diseases is increasing in association with epidemics of obesity in developed countries. A review on obesity, insulin resistance, arterial hypertension and polycystic ovary syndrome is done.